Microhabitat utilisation and coexistence strategies of sucker fish Garra mullya (Sykes, 1839) and zodiac loach Mesonoemacheilus triangularis (Day, 1865) in a wooded hill stream of Southern Kerala, India - Thomas, Ruby; Thomas K., Raju (Macedonian Journal of Ecology and Environment, 2024)
The habitat requirements of fishes vary with their biological and physiological processes. In this study conducted from March 2019 to February 2020, we focused on Garra mullya (Sykes, 1839) and Mesonoemacheilus triangularis (Day, 1865) in a wooded hill stream of the Pamba river basin in southern Kerala, India. These species were selected due to their ecological significance and prevalence within the freshwater ecosystems of the region. Our investigation aimed to identify and quantify microhabitat availability, utilisation patterns, and niche partitioning mechanisms influenced by trophic requirements, morphological and physiological characteristics, and stream biochemical conditions. Our focus was on fifteen environmental descriptors and attributes that operate on the microhabitat scale. Principal Component Analysis (PCA) and Pearson correlation were employed to reveal the habitat selectivity and association of species with multiple environmental variables at the focal point position of each observed fish. Microhabitat selection in G. mullya and M. triangularis was driven by trophic requirements, morphological and physiological characteristics of the fish, and biochemical conditions of the stream. G. mullya inhabited cobble and rubble-dominated microhabitats and favoured closer proximity to shelter and banks. M. triangularis, on the other hand, preferred gravel-filled microhabitats and was found to use locations near banks and shelters, more frequently. The coexistence of G. mullya and M. triangularis along the water column can be attributed to resource allocation and substrate variability.